Hypoxia-induced lipid changes and their effect on innate immunity - Archer Slone, Emily E. (Kansas State University, 2013)
Ischemia/reperfusion (IR) events result in severe tissue damage and often death. The complex network of molecular and cellular mechanisms that contributes to intestinal IR-induced pathology has hindered a comprehensive understanding of IR-induced injury and limited the success of medical intervention. Although several of the mechanisms contributing to intestinal IR-induced injury have been identified, the initiating event(s) remains unclear. Mouse models have been instrumental in the unraveling of the many components and interactions that ultimately result in tissue damage. It is clear that leukocyte infiltration, complement activation, eicosanoid and pro-inflammatory cytokine production are involved. Toll-like receptors and antibodies also play critical roles. Based on the literature, and especially data demonstrating a significant role for anti-phospholipid antibodies, we hypothesized that ischemia induces phospholipid alterations that result in the exposure of a neoantigen which is recognized by anti-phospholipid antibodies. Furthermore, we hypothesized that endothelial cells are the primary cell type involved in the initial molecular events that result in intestinal IR-induced pathology. A mouse model of intestinal IR as well as an in vitro cell culture system was used to explore these hypotheses. Mass spectrometry-based lipidomics was utilized to assess lipid responses to IR and hypoxia/re-oxygenation (HR). No inherent differences in intestinal phospholipid composition were found between wildtype and several strains of knock-out mice. It was determined that the lack of antibody production by Rag-1[superscript]-[superscript]/[superscript]- mice is responsible for protection against intestinal IR-induced injury, as antibody is needed to induce prostaglandin E[subscript]2 production, through up-regulation of cyclooxygenase 2 transcription. Unexpectedly, the presence or absence of toll-like receptor 9 was found to be inconsequential for tissue damage caused by intestinal IR. The results of several analyses point to endothelial cells as being directly involved in IR-induced pathology. Importantly, the activation of phospholipid scramblase 1 has been identified as a potential molecular mechanism by which subsequent molecular and cellular responses are elicited as a consequence of IR.
Keywords: Ischemia; Endothelium; Hypoxia; Phospholipid scramblase 1; Biology (0306); Biology, Animal Physiology (0433)